Uncertainty matters: Bayesian modeling of bicycle crashes with incomplete exposure data. (February 2022) - Xu, Pengpeng; Bai, Lu; Pei, Xin; Wong, S.C.; Zhou, Hanchu
Highlights: One major challenge of bicycle safety is lack of complete exposure data. A simultaneous-equation model was proposed to tackle incomplete exposure data. Our model can reveal link of built environment, cycling levels, and bicycle crashes. Our model is promising in imputation of missing exposure values. Ignoring uncertainty in exposure results in biased inferences. Abstract: Background: One major challenge faced by neighborhood-level bicycle safety analysis is the lack of complete and reliable exposure data for the entire area under investigation. Although the conventional travel-diary surveys, together with the emerging smartphone fitness applications and bike-sharing systems, provide straightforward and valuable opportunities to estimate territory-wide bicycle activities, the obtained ridership suffers inherently from underreporting. Methods: We introduced the Bayesian simultaneous-equation model as a sound methodological alternative here to address the uncertainty arising from incomplete exposure data when modeling bicycle crashes. The proposed method was successfully fitted to a crowdsourced dataset of 792 bicycle–motor vehicle (BMV) crashes aggregated from 209 neighborhoods over a 3-year period in Hong Kong. Results: Our analysis empirically demonstrated the bias due to omission of activity-based exposure measures or to the direct use of cycling distance extracted from the travel-diary survey without correcting for incompleteness. By modeling bicycle activities and the frequency of BMV crashes simultaneously, we also provided new evidence that an expansion of bicycle infrastructure was likely associated with a significant increase in cycling levels and a substantial reduction in the risk of BMV crashes, despite a slight increase in the absolute number of BMV crashes. Conclusions: Our approach is promising in adjusting for the uncertainty in raw exposure data, extrapolating the missing exposure values, and untangling the linkage among built environment, bicycle activities, and the frequency of BMV crashes within a unified framework. To promote safer cycling, designated facilities should be provided to consecutively separate cyclists from motor vehicles.